Esakia : Kyushu University Publications in Entomology. (Esakia ;, 1984)
Contents : Ecological studies on insect species diversities and productivities in the highland agricultural systems of PNG (Hirashima, Y) - New species of Dicraeus (Diptera, Chloropidae) from New Guinea and New Ireland (Ismay, J.W) - Eleven new Helina-species collected on wet stones along mountain streams in PNG (Diptera : Muscidae)(Shinonaga, S.) - Plant associated alticinae from the Bismarck Range, PNG (Coleoptera : Chrysomelidae)(Samuelson, G.A.) - Distributionof chrysomelid pests associated with certain agricultural plants in PNG (Coleoptera) (Kimoto, S.) - Two new species of prosopiteroides from PNG (Hymenoptera, Colletidae, hylaeus) (Hirashima, Y.).